FABP2は腸管神経細胞のαシヌクレイン病理において重要な分子である - 関森, 智紀; 川畑, 伊知郎; 佐々木, 拓哉; 福永, 浩司 (日本薬理学会年会要旨集, 2023)
[Background/Purpose] Parkinson's disease and dementia with Lewy bodies are caused by neuronal cell death induced by α-Synuclein (α-Syn) accumulation. We have previously reported that fatty acid binding protein (FABP) plays an essential role to the α-syn pathology in the brain. Recently, it has become clear that pathological α-Syn is transmitted from the gut to the brain via the vagus nerve. However, the detailed mechanism of such α-Syn propagation is still unclear. Accordingly, we focused on the process of α-Syn uptake into enteric neurons, and tried to identify the key molecules of that process. [Methods] We used primary cultured neurons from murine small intestinal myenteric plexus. We treated fluorescence labeled α-Syn PFF to the primary neurons, and observed α-Syn uptake by immunocytochemistry. [Results] Intracellular uptake of α-Syn into primary neurons was observed. Interestingly, taken up α-Syn was colocalized with intestinal-FABP (FABP2). Furthermore, the fluorescence intensity of taken up α-Syn correlated with that of the 2nd antibody against anti-FABP2 1st antibody. [Conclusion] This results indicates that FABP2 is involved in the process of the intracellular uptake and/or accumulation of α-Syn. Therefore, FABP2 is an important molecule for elucidating the mechanism of α-Syn pathology in the gut.